Cystopexy raises the post-operative complication rate during laparoscopic hysterectomy for uterine prolapse - Ronsini, Carlo; Andreoli, Giada; Torella, Marco; Romeo, Paola; Sarpietro, Giuseppe; Cianci, Stefano (Frontiers in Surgery, 2025)
ObjectivesThis study aims to compare the outcomes of laparoscopic colposuspension sec Shull (LCSS) and laparoscopic colposacropexy (LCSP) with and without the addition of cystopexy for the treatment of pelvic organ prolapse (POP) in terms of postoperative complications, recurrence rates, and overall effectiveness.Materials and methodsA retrospective case-control analysis was conducted on women treated for grade 3–4 POP-Q uterine prolapse at the Academic Departments of Gynaecology and Obstetrics of “G. Martino” of Messina, Italy, and “L. Vanvitelli” of Napoli, Italy, between November 2020 and February 2022. Group A consisted of patients who underwent laparoscopic hysterectomy followed by LCSS or LCSP without cystopexy. At the same time, Group B included patients who had the same procedures with the addition of cystopexy. Data on complications were collected using the Clavien-Dindo classification, and prolapse recurrence was monitored according to the POP-Q system. Statistical analysis was performed using Fisher's exact, Chi-squared, and Wilcoxon rank-sum tests.ResultsA total of 148 patients were included, with 125 in Group A and 23 in Group B. Group B showed a significantly higher rate of postoperative complications (16%) compared to Group A (2.4%) (p = 0.016), with an Odds Ratio of 7.62 (95% CI 1.59–36.51, p = 0.0017). No significant difference between the groups was found in the recurrence rate of prolapse at 24 months (p > 0.9).ConclusionAdding cystopexy to LCSS or LCSP increases the risk of postoperative complications without reducing prolapse recurrence rates. Further research is needed to identify patients who may benefit from cystopexy and to evaluate its impact on stress incontinence and patient satisfaction.